Breeding for water use efficiency - De Almeida Silva, Marcelo [UNESP] (2013)
Among environmental factors, drought is the principal factor that limits global agricultural production. Many global agricultural regions are already suffering serious problems with water shortage and this scenario suggests that greater efforts are required in the development of alternatives for sustainable agriculture, such as the selection of cultivars that are efficient in the use of water. Water use efficiency (WUE) is the most important component of drought adaptation. In this chapter, WUE will be emphasized because of its greater importance and the possibility of obtaining genotypes that respond to environmental improvement or to the availability of water when it occurs. For this purpose the following topics will be addressed: germplasm, genetic variability, relationship between characteristics, inheritance and maternal effect, oxidative stress, stress induction, selection strategies and breeding methods, and biotechnology applied to the breeding of WUE.